The rise and rise of Islamic banking - Parker, Mushtak (The Middle East, 1987)
An outline of the growth of the Islamic banking system since its inauguration in 1975 together with a detailed account of the performance of the more prominent banks. Light is shed in particular on the banks' international connections and how banks across the world are adapting. (DÜI-Asd)